2007
DOI: 10.1002/eqe.685
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the weightiness of site effects on reinforced concrete (RC) building seismic behaviour: The Adra town example (SE Spain)

Abstract: The damage distribution in Adra town (south-eastern Spain) during the 1993 and 1994 Adra earthquakes (5.0 magnitude), that reached a maximum intensity degree of VII (European Macroseismic Scale (EMS scale)), was concentrated mainly in the south-east zone of the town and the most relevant damage occurred in reinforced concrete (RC) buildings with four or five storeys. In order to evaluate the influence of ground condition on RC building behaviour, geological, geomorphological and geophysical surveys were carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
23
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
(16 reference statements)
8
23
0
4
Order By: Relevance
“…For European buildings, our result is strikingly similar to that obtained by Navarro et al (2007) for Spanish RC buildings, who proposed the relationship T = 0.049N, with N equal to the number of floors (assuming 3 m as the inter-storey height). We compared our relationship also with the provisions of EC8 (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For European buildings, our result is strikingly similar to that obtained by Navarro et al (2007) for Spanish RC buildings, who proposed the relationship T = 0.049N, with N equal to the number of floors (assuming 3 m as the inter-storey height). We compared our relationship also with the provisions of EC8 (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The height-period relationship we determined is robust and very similar to another relationship proposed for Southern European buildings by Navarro et al (2007). Confirming the results of Gallipoli et al (2008), who analysed a first subset of our data set, we found that our relationship is very different from European code provisions (EC8).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…3; Fig. 6a) is occupied by Pleistocene colluvials and Pliocene marine terraces over the Precambrian low-permeability metapelitic bedrock (Navarro et al, 2007). Coarse-grained marine terraces form a discontinuous confined perched aquifer from which diffuse discharge contributes to local streams supporting GDE .…”
Section: Discussionmentioning
confidence: 99%
“…3; Fig. 4a) is located in the discharge area of the Adra River delta (ARD hereafter), a regional aquifer of 60 m in thickness composed of Holocene alluvial and fluvial formations, Pleistocene colluvials, Pliocene marine terraces, and Miocene calcarenites over a Precambrian low-permeability crystalline (metapelitic) bedrock (Navarro et al, 2007). Plio-Quaternary formations discharge to the sea and GDE .…”
Section: Discussionmentioning
confidence: 99%